Photocatalytic activity of bismuth silicate heterostructures synthesized via surfactant mediated sol-gel method. (1st November 2019) - Karthik, K.; Devi, K.R Sunaja; Pinheiro, Dephan; Sugunan, S.
Abstract: A surfactant mediated sol-gel method is employed to synthesize bismuth silicate heterostructures with tunable morphologies and properties. The synthesized nanoparticle samples were characterized by XRD, FTIR Spectroscopy, SEM-EDAX and UV-DRS. The synthesized bismuth silicates exhibit excellent photodegradation against malachite green and rhodamine B dyes in the aqueous medium. Bismuth silicates (10% SiO2 -Bi2 O3 ) show superior photocatalytic property and outstanding reusability compared to pure bismuth oxide. The kinetics of the photodegradation of the dyes shows that the reaction follows first-order kinetics with the regression coefficient of 0.99. Thus, enabling Bismuth silicates heterostructures practical application as a photocatalyst for clean water.